2009
DOI: 10.1128/jvi.01311-09
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Levels of Innate Immune Modulators in Lymph Nodes and Blood Are Associated with More-Rapid Disease Progression in Simian Immunodeficiency Virus-Infected Monkeys

Abstract: ؉ cells were not increased, nor were the SIV RNA levels decreased. In peripheral blood, increased OAS and CXCL10 expression were elevated in SIV ؉ monkeys that progress the fastest to simian AIDS. Our results indicate that higher IFN-␣, OAS, CXCL9, and CXCL10 mRNA expression in LN was associated with rapid disease progression and a LN environment that may favor SIV replication. Furthermore, higher expression of CXCL10 and OAS in peripheral blood could potentially serve as a diagnostic marker for hosts that are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 67 publications
4
43
0
1
Order By: Relevance
“…Lederer et al (23) also observed higher levels of IFN gene in the colon of nonpathogenic AGMs compared to pathogen SIV-infected pigtail monkeys. More recently, mRNA expression of four immune modulators-IFN-␣, oligoadenylate synthetase, CXCL9, and CXCL10-was positively associated with disease progression within the LN tissues of SIV-infected RMs of Indian origin (13) and consistent with the profile of mRNAs observed in lymphatic tissue of untreated HIV-infected persons during the acute phase (26). Thus, depending on the anatomical location, the levels of expression of IFN-associated genes may distinguish pathogenic and nonpathogenic infections.…”
Section: Discussionsupporting
confidence: 53%
“…Lederer et al (23) also observed higher levels of IFN gene in the colon of nonpathogenic AGMs compared to pathogen SIV-infected pigtail monkeys. More recently, mRNA expression of four immune modulators-IFN-␣, oligoadenylate synthetase, CXCL9, and CXCL10-was positively associated with disease progression within the LN tissues of SIV-infected RMs of Indian origin (13) and consistent with the profile of mRNAs observed in lymphatic tissue of untreated HIV-infected persons during the acute phase (26). Thus, depending on the anatomical location, the levels of expression of IFN-associated genes may distinguish pathogenic and nonpathogenic infections.…”
Section: Discussionsupporting
confidence: 53%
“…Recent publications (8)(9)(10)(11)(12)) highlight a distinctive downregulation of the interferon response after SIV infection of natural host species, such as sooty mangabeys and African green monkeys. In contrast, SIV infection of the pathogenic models of rhesus or pig-tailed macaque is character- Gene set enrichment analysis of human VNPs and SIVinfected sooty mangabeys.…”
Section: Figurementioning
confidence: 99%
“…This profile of tolerance of viral replication is reminiscent of the pattern of SIV infection in the natural host. The importance of such model for the understanding of HIV/AIDS pathogenesis has been underscored by studies in sooty mangabeys and in African green monkeys (8)(9)(10)(11)(12). Sooty mangabeys have nonprogressive disease despite chronic virus replication that is characterized by low levels of immune activation, while pathogenic SIV infection of rhesus macaques is associated with chronic immune activation.…”
Section: Introductionmentioning
confidence: 99%
“…Increased CXCL10 RNA levels in plasma and lymph nodes has been associated with rapid HIV disease progression and viral rep-lication (38)(39)(40). CXCL10 also acts as a chemoattractant for monocytes/macrophages, T cells, natural killer cells, and dendritic cells.…”
Section: Cytokine/chemokine Responses In Cd8 ؉ T Cells During Acute Smentioning
confidence: 99%